Luminescence and scintillation properties of rare-earth-doped LaAlO3 single crystals. (February 2019) - Pejchal, Jan; Barta, Jan; Trojek, Tomas; Kucerkova, Romana; Beitlerova, Alena; Nikl, Martin
Abstract: LaAlO3 perovskite single crystals doped with Ce, Eu or Tb have been grown by micro-pulling-down method. X-ray diffraction analysis confirmed low-temperature rhombohedric phase. Energy-dispersive Laue mapping revealed sub-grains in the grown crystals. For the Ce-doped crystals, very low radioluminescence efficiency was found and the observed emission was ascribed to defects. Photoluminescence spectra were significantly different from the radioluminescence ones. They were significantly quenched at room temperature and the related luminescence showed also unusually high Stokes shift. High radioluminescence efficiency was found for the Tb-doped samples and especially for the Eu-doped ones, which would point to the fact that in LaAlO3 the scintillation process is more favorable for the luminescence ions which tend to capture an electron first. Highlights: Morphology of the grown rare-earth-doped LaAlO3 crystals was studied. Role of the growth atmosphere explained by its influence on Ce valence state. Origin of radioluminescence explained by defect emission in Ce-doped crystals. High radioluminescence efficiency found for Eu-doped crystals.